MicroRNA-483-5p Predicts Poor Prognosis and Promotes Cancer Metastasis by Targeting EGR3 in Nasopharyngeal Carcinoma - Li, Xi-Zhao; Tu, Yi-Jun; Zhou, Ting; Zhang, Jiang-Bo; Xiao, Ruo-Wen; Yang, Da-Wei; Zhang, Pei-Fen; You, Peng-Tao; Zheng, Xiao-Hui (Frontiers in Oncology, 2021)
Background: MicroRNAs as small non-coding RNAs play an important role in tumorigenesis. MiR-483-5p was found to have a significant increase as a diagnostic biomarker of nasopharyngeal carcinoma (NPC), not only in plasma from NPC patients, but also in tumor cell lines and biopsy tissues in our previous study. However, its function and mechanism in NPC is still unclear. Methods: Tissue microarray including 178 primary NPC and 35 adjacent noncancerous nasopharyngeal mucosal tissues were used to further validate the over-expression of miR-483-5p. Wound healing and invasion assays were conducted to verify its biological function. RNA-seq and dual luciferase reporter assay was performed to explore its target, and it was verified in fresh biopsy tissues from 23 NPC patients and 9 patients with chronic nasopharyngitis. Results: MiR-483-5p was highly expressed in NPC tissues than its expression in adjacent noncancerous tissues. It was found to have a significant correlation with poor overall survival (OS) (hazard ratio (HR), 2.89; 95% confidence interval (CI), 1.00-8.35; p = 0.041) and PFS (HR, 1.95; 95%CI, 1.06-3.60; P=0.029) of NPC patients. Silence of its expression inhibited the migratory and invasive capacities of NPC cells in vitro. EGR3 (early growth response 3) was identified as a direct target, and inhibiting miR-483-5p expression markedly enhanced EGR3 expression at both mRNA and protein levels. Besides, a significant decrease of EGR3 expression was found in fresh biopsy tissues from NPC patients, in contrast to miR-483-5p expression. Further, directly decreasing EGR3 expression could enhance the NPC cell's migration and invasion. Conclusion: The newly identified miR-483-5p/EGR3 pathway provides further insights into the development and metastasis of NPC, and may provide a potential therapeutic target for NPC treatment in order to improve NPC patients' survival.